Estimate of the maximum of modulus of generalized solutions of the first boundary-value problem for degenerate parabolic equations - Kolody, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 1997)
We study parabolic equations of the divergent form with degeneration. We have obtained an estimate for the maximum of modulus of generalized solutions of the first boundary-value problem with a zero on the parabolic boundary.